Influência da viscosidade do condicionador ácido na dentina radicular sobre a resistência de união de um sistema de cimentação adesivo. Avaliação por teste de push-out e MEV - Salas, Mabel Miluska Suca (2005)
Actually different alternatives to restored teeth with endodontical treatment are propose, otherwise with the advented of adhesive systems their use as luting endodontical cements and bonding resin cement for fiber posts are common. However the inherent characteristics behavior of these materials and the different variances presented at root canal, turns them sensible to failure. The aime of the study was to evaluated: a) the influence of two luting cements: containing eugenol (Endofill) and containing resin materials (Ahplus) on dentin bonding strength using push-out test at cervical, medium and apical root dentin regions, using two different 37% phosphoric acid viscosities: gel and liquid: b) the effect of the total-etching acid process on the pattern observed of the conditioned dentine substrate, c) Characterize the dentinal surface at different root regions d) Classify the fracture patterns between the substrate and the resin cement at three root regions. One hundred and four uniradicular teeth without caries lesions, extracted by orthodontics or periodontal reasons, with 7mm of diameter and 14mm of length were selected, disinfected in 0,5% chloramine and storage in distillated water at 5ºC. Endodontical canal treatments were performed using the Step-back technique and obturated with Endofill and AHplus. The preparation of the post space was 11mm depth using standardized rotary instruments. The total-etching with the gel and liquid acid were performed. The fiber posts were marked at the same depth, cuted, dry and silanized. Then two coats of Prime&bond 2,1 previously mixed with the self-cure activator, were applied at the post surface and into de root canal, after 1 minute the post were photocured (halogen light intensity of 450mW). The resin cement was mixed and placed into de canal using a lentuloespiral instrument. The posts were placed and a static force of 5kg for 10 minutes were applied, after words both adhesive and cement were photocured for 40 seconds, storage for 24 h in 37ºC, and embedded in a poliestyren resin. Cross-sectional cuts were obtained for the push-out test. The test were performed at a crosshead speed of 0,5mm/min, and a plane 20 cylindrical point was applied at the post centre. The maxim load was calculated in Mpa. The adhesive area was calculated using a tapered-cone shaped formula. The results were subjected to statistical analysis using a ANOVA test for multiple variables and a Pos Doc test(p<0,05) Statistically significant differences were detected between all the evaluated criterias: acids, cements and regions, and when they were inter-relationated between them. It was concluded that the use of 37% of phosphoric acid in a liquid form, allows a better penetration into the root canal, a uniform decalcification, consequently enhancing the bonding strength of the root dentine, particularly at apical region.